Impact of Comprehensive Health Insurance affiliation on mortality in children under one year: an analysis of the Demographic and Health Survey 2010–2022 in Peru - Espinola-Sánchez, Marcos; Campaña-Acuña, Andres; Urrunaga-Pastor, Diego; Maguiña, Jorge L.; Jumpa, Manuel; Ugarte-Ubillus, Oscar (Frontiers in Public Health, 2025)
ObjectiveTo assess the impact of Comprehensive Health Insurance (CHI) coverage on mortality in children under 1 year of age in the Peruvian population from 2010 to 2022. Additionally, the study evaluated how CHI affects infant mortality according to wealth quintiles in the Peruvian population.MethodsA causal inference analysis with observational data was applied, employing propensity score matching. Participants included children under 1 year of age, surveyed through the National Demographic and Family Health Survey (ENDES) from 2010 to 2022. Variables measured included CHI affiliation and death in children under 1 year. Methods such as inverse probability weighting adjusted by regression, Average Treatment Effect on the Treated (ATET) estimation, and endogeneity test were applied.ResultsThe study population consisted of 26,319 children under 1 year, with 11,922 not affiliated with CHI and 14,397 affiliated. The ATET analysis as an exogenous treatment of CHI showed a significant reduction in infant mortality in the overall population of children by 12.6% (95% CI: 12.1 to 13.1%), in the poverty subgroup by 15.6% (95% CI: 14.9 to 16.3%), and in the non-poverty subgroup by 6% (95% CI: 5.5 to 6.4%). However, endogeneity was observed in the ATET for the non-poverty subgroup and for the overall population of children.ConclusionCHI affiliation contributes to reducing mortality in children under 1 year in the population with low economic incomes in Peru. However, this relationship is inconclusive for the general population and for the population with medium and high incomes, highlighting the importance of considering socioeconomic, demographic, and other insurance factors.